Requirements for temporal BDA implementation methodology in organizations - Mach-Król, Maria (Wymagania dla metodyki implementacji temporalnej BDA w organizacjach, 2019)
The article is devoted to the problem of temporal big data analytics (BDA) in organizations in the context of the challenges arising from the business environment. The research problem originates from the multiplicity of existing approaches to implementing big data, from the multiplicity of concepts underlying these approaches, as well as from the lack of temporality context in the existing proposals. It is thus necessary to review and order the big data methodologies and strategies. The article also characterizes the challenges for an effective temporal BDA, and on this basis a set of requirements is formulated which must be met by the temporal big data analytics implementation methodology in organizations. For these purposes, firstly, a critical analysis of literature was used as the research method, secondly, methods of creative thinking, synthesis and analysis were used
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 1 (51), s. 44-54
Keywords: BDA; implementation methodology; maturity model; temporality; motodyka implementacji; model dojrzałości; temporalność